Clinical and radiological outcomes of jumbo cup in revision total hip arthroplasty: A systematic review - Wang, Qiuyuan; Wang, Qi; Liu, Pei; Ge, Juncheng; Zhang, Qidong; Guo, Wanshou; Wang, Weiguo (Frontiers in Surgery, 2022)
Abstract Introduction Many studies have reported the clinical outcomes of jumbo cup in revision total hip arthroplasty (rTHA) with acetabular bone defect. We conducted a systematic review to access the survivorship, clinical and radiological outcomes of jumbo cup in rTHA. Methods A systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A comprehensive literature search from PubMed, MEDLINE, EMBASE, and the Cochrane Database of Systematic Reviews was performed with the keywords (“revision” OR “revision surgery” OR “revision arthroplasty”) AND (“total hip arthroplasty” OR “total hip replacement” OR “THA” OR “THR”) AND (“jumbo cup” OR “jumbo component” OR “extra-large cup” OR “extra-large component”). Studies reporting the clinical or radiological outcomes were included. The basic information, radiological and clinical results of these studies were extracted and summarized for analysis. Results Nineteen articles were included in the systematic review. The analysis of clinical result included 953 hips in 14 studies. The re-revision-free survivorship of jumbo cup was 95.0% at the mean follow-up of 9.3 years. Dislocation, aseptic loosening and periprosthetic joint infection were the top three complications with the incidence of 5.9%, 3.0% and 2.1%, respectively. The post-revision hip center was relatively elevated 10.3 mm on average, the mean postoperative leg-length discrepancy was 5.4 mm. Conclusion Jumbo cup is a favorable option for acetabular bone defect reconstruction in rTHA with satisfying survivorship and acceptable complication rate.